Etiología de bronquiolitis en niños hospitalizados en el sureste de España - Salvador García, C. (An Pediatr (Barc), 2012)
BACKGROUND: Bronchiolitis is the most common respiratory disease in children under 2 years-old and a major cause of hospitalization in young children, especially during the winter. OBJECTIVES: To determine the prevalence and etiology of bronchiolitis in south-east of Spain. STUDY DESIGN: A prospective study was conducted during the bronchiolitis season (December-April). Children below 18 months-old admitted to the hospital for a first bronchiolitis episode were included. Nasopharyngeal aspirates were analysed by reverse transcription polymerase chain reaction (RT-PCR) respiratory syncytial virus. RESULTS: A total of 235 children were included during this period, and 235 RT-PCR were performed. A total of 287 viruses were detected in nasopharyngeal aspirates from 204 infants. Respiratory syncytial virus was the virus detected more frequently, followed by rhinovirus. Co-infections were found in the 36% of children. CONCLUSIONS: Respiratory viruses were detected in most of the children below 18 months-old hospitalised with bronchiolitis, and 36% of them showed a mixed infection.